Detection of Heavy metals in Fruits and Vegetables Available in the Market of Quetta City - Khair Un Nisa; Samiullah; Khan, Naqeebullah; Attiq-ur-Rehman (Al-Nahrain Journal of Science, 2020)
This study is conducted for the determination of heavy metals concentration like Fe, Ni, Mn, Co, Cd, Cu and Pb in five edible vegetables (Cauliflower, Cabbage, Cucumber, Lady finger and Tomato), five edible Fruits (Water melon, peach, Banana, Mango (Sindhri & Langra) and apple) and peel of all these Fruits and endocarp of apple. Samples were purchased from the Local Market of Quetta city (Capital of Balochistan). Atomic Absorption Spectrophotometer ((FAAS, Thermo - Electron Corporation, S4 AA System, Ser. No, GE711544, China) double beam and deuterium background hollow cathode lamps of Fe, Pb, Cd, Co, Cu, Ni and Mn were used at specific wavelengths for the determination of heavy metals concentration. Samples were run three times and at least three or four standards are used for each metal analysis. Concentration of Fe, Mn, and copper were very much below the permissible limits defined by WHO/FAO. Concentration of Ni was found at toxic level in cucumber. Concentration of Cd was above the safe value in all samples except banana fruit given by WHO/FAO. Concentration of Co was found above the limit defined by ASTDR 1994 in all the samples. Concentration of Pb with respect to the (China food hygiene standards 1994) 0.2mg/kg and WHO/FAO 0.3mg/kg is above the limit in all samples but it found very high in Tomato, Cabbage, Cucumber, Peach and Watermelon. The overall result of this study reveals that the samples of vegetable and fruits are highly contaminated with heavy metals Co, Pb, Ni and Cd due to the usage of drainage water for watering them and their consumption can cause hazardous effect on human health.